2020
DOI: 10.5435/jaaos-d-20-00391
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for the Care of Pediatric Orthopaedic Patients During the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has necessitated modifications to pediatric orthopaedic practice to protect patients, families, and healthcare workers and to minimize viral transmission. It is critical to balance the benefits of alterations to current practice to reduce the chances of COVID-19 infection, with the potential long-term impact on patients. Early experiences of the pandemic from orthopaedic surgeons in China, Singapore, and Italy have provided the opportunity to take proactive and preventive measures to prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
7

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 11 publications
1
71
0
7
Order By: Relevance
“…During COVID-19 pandemic, with parks closed recent spike in purchase of home play equipment and trampolines has been registered. Consequently, the lockdown per se did not prevent all injuries [9].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…During COVID-19 pandemic, with parks closed recent spike in purchase of home play equipment and trampolines has been registered. Consequently, the lockdown per se did not prevent all injuries [9].…”
Section: Discussionmentioning
confidence: 96%
“…This nding is probably due to the fact that younger children are less aware of the risks of injury and they probably have an experimental behavior. Farrell et al [9] reported that during the SARS outbreak in 2003, ER visits declined by 21% (95% CI, 18%-24%) over the 4-week study period.…”
Section: Discussionmentioning
confidence: 99%
“…Delays of operative intervention in elective cases although temporary, might extend for months as a best estimate. Patients should be offered sound alternatives to assist them bear the anticipated waiting times, this could be in the form of optimized medical treatment, individualized non-surgical options through multidisciplinary approaches, supportive online counseling, psychological support, and in pediatric patients engaging families and stressing on safety measures [40][41][42].…”
Section: What Should Be Offered To Patients As An Alternativementioning
confidence: 99%
“…In any case, telemedicine must be encouraged whenever possible. Follow up imaging should be taken near the locality of the patient and e-mailed to the institute, only if likely to make a significant change to care [7,8].…”
Section: Outpatient Carementioning
confidence: 99%
“…In case of elective surgery, a strict priority must be maintained in the waiting list, especially if the duration of the pandemic period cannot be precisely estimated [7,8]. The Advisory Board of the SITOP has provided a panel of priority levels in order to safely schedule deferrable surgical treatments, reducing the risk of missing children who require non postponable operations, during the pandemic and post peak period (see Table 2).…”
Section: Surgical Carementioning
confidence: 99%